A consistent description of kinetics and hydrodynamics of systems of interacting particles by means of the nonequilibrium statistical operator method - Tokarchuk, M.V.; Omelyan, I.P.; Kobryn, A.E. (Condensed Matter Physics, 1998)
A statistical approach to a self-consistent description of kinetic and hydrodynamic processes in systems of interacting particles is formulated on the
basis of the nonequilibrium statistical operator method by D.N.Zubarev. It
is shown how to obtain the kinetic equation of the revised Enskog theory
for a hard sphere model, the kinetic equations for multistep potentials of interaction and the Enskog-Landau kinetic equation for a system of charged
hard spheres. The BBGKY hierarchy is analyzed on the basis of modiﬁed
group expansions. Generalized transport equations are obtained in view
of a self-consistent description of kinetics and hydrodynamics. Time correlation functions, spectra of collective excitations and generalized transport
coefﬁcients are investigated in the case of weakly nonequilibrium systems
of interacting particles. Представлено один із статистичних підходів узгодженого опису кінетичних та гідродинамічних процесів систем взаємодіючих частинок,
що сформульований на основі методу нерівноважного статистичного оператора Д.М.Зубарєва. Показано, як із ланцюжка рівнянь ББГКІ
з модифікованими граничними умовами отримуються кінетичне рівняння ревізованої теорії Енскога для моделі твердих сфер, кінетичне рівняння для багатосходинкового потенціалу та кінетичне рівняння Енскога-Ландау для моделі заряджених твердих сфер. Проаналізовано ланцюжки рівнянь ББГКІ на основі модифікованих групових
розкладів. Отримано узагальнені рівняння переносу узгодженого
опису кінетики та гідродинаміки. Для випадку слабо нерівноважних
систем класичних взаємодіючих частинок при взаємному врахуванні кінетичних та гідродинамічних процесів досліджено часові кореляційні функції, спектр колективних збуджень та узагальнені коефіцієнти переносу.